Mineral types and organic matters of the Ordovician-Silurian Wufeng and Longmaxi Shale in the Sichuan Basin, China: Implications for pore systems, diagenetic pathways, and reservoir quality in fine-grained sedimentary rocks. (September 2017) - Zhao, Jianhua; Jin, Zhijun; Jin, Zhenkui; Hu, Qinhong; Hu, Zongquan; Du, Wei; Yan, Caina; Geng, Yikai
Abstract: Mineral types (detrital and authigenic) and organic-matter components of the Ordovician-Silurian Wufeng and Longmaxi Shale (siliceous, silty, argillaceous, and calcareous/dolomitic shales) in the Sichuan Basin, China are used as a case study to understand the control of grain assemblages and organic matter on pores systems, diagenetic pathway, and reservoir quality in fine-grained sedimentary rocks. This study has been achieved using a combination of petrographic, geochemical, and mercury intrusion methods. The results reveal that siliceous shale comprises an abundant amount of diagenetic quartz (40–60% by volume), and authigenic microcrystalline quartz aggregates inhibit compaction and preserve internal primary pores as rigid framework for oil filling during oil window. Although silty shale contains a large number of detrital silt-size grains (30–50% by volume), which is beneficial to preserve interparticle pores, the volumetric contribution of interparticle pores (mainly macropores) is small. Argillaceous shale with abundant extrabasinal clay minerals (>50% by volume) undergoes mechanical and chemical compactions during burial, leading to a near-absence of primary interparticle pores, while pores preserved between clay platelets are dominant with more than 10 nm in pore size. Pore-filling calcite and dolomite precipitated during early diagenesis inhibit later compaction in calcareous/dolomitic shale, but the cementation significantly reduces the primary interparticle pores. Pore-throat size distributions of dolomitic shale show a similar trend with silty shale. Besides argillaceous shale, all of the other lithofacies are dominated by OM pores, which contribute more micropores and mesopores and is positively related to TOC and quartz contents. The relationship between pore-throat size and pore volume shows that most pore volumes are provided by pore throats with diameters <50 nm, with a proportion in the order of siliceous (80.3%) > calcareous/dolomitic (78.4%) > silty (74.9%) > argillaceous (61.3%) shales. In addition, development degree and pore size of OM pores in different diagenetic pathway with the same OM type and maturity show an obvious difference. Therefore, we suggest that the development of OM pores should take OM occurrence into account, which is related to physical interaction between OM and inorganic minerals during burial diagenesis. Migrated OM in siliceous shale with its large connected networks is beneficial for forming more and larger pores during gas window. The result of the present work implies that the study of mineral types (detrital and authigenic) and organic matter-pores are better understanding the reservoir quality in fine-grained sedimentary rocks. Highlights: Origin of detrital components and diagenesis are studied. Lithfacies with different components shows differences in diagenetic pathway. Early authigenic quartz controls the distribution of migrated OM in siliceous shale. Pore-size distributions of dolomitic shale shows the similar trend with silty shale.